2015
DOI: 10.3390/ijgi4031584
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Analysis of Spatial Accessibility to Primary Health Care in Bhutan

Abstract: Geographic information systems (GIS) can be effectively utilized to carry out spatio-temporal analysis of spatial accessibility to primary healthcare services. Spatial accessibility to primary healthcare services is commonly measured using floating catchment area models which are generally defined with three variables; namely, an attractiveness component of the service centre, travel time or distance between the locations of the service centre and the population, and population demand for healthcare services. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
74
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(78 citation statements)
references
References 20 publications
1
74
0
3
Order By: Relevance
“…Other methods using FCA approach are also available to measure geographic accessibility to healthcare services [6267]. An in-depth review of the accessibility methods those are build on the FCA model can be found here [68, 69]. In short, there are two significant improvements to the original 2SFCA method that was introduced by Luo and Wang (36): 1) account for distance-decay within a catchment [57, 70] and 2) usage of variable catchment sizes [70, 71].…”
Section: Methodsmentioning
confidence: 99%
“…Other methods using FCA approach are also available to measure geographic accessibility to healthcare services [6267]. An in-depth review of the accessibility methods those are build on the FCA model can be found here [68, 69]. In short, there are two significant improvements to the original 2SFCA method that was introduced by Luo and Wang (36): 1) account for distance-decay within a catchment [57, 70] and 2) usage of variable catchment sizes [70, 71].…”
Section: Methodsmentioning
confidence: 99%
“…The spatial accessibility indicated that 205 sub-districts show great disparities in health care access throughout the country. The research in Bhutan indicates that in 2013, 24% of Bhutan's populations had poor access to primary health care service, 66% had medium-level access, and only 10% had good access [Jamtsho et al, 2015].…”
Section: Environmental Exposure Risk Factormentioning
confidence: 99%
“…Since the 1980s, many scholars have studied accessibility in terms of the spatial layout of public service facilities (schools, hospitals, shopping centers, etc.) [1][2][3][4][5][6]; these studies use accessibility results to assess the equity of social and economic activities, as well as the balance of public service resource allocation within cities. General hospitals are one of the most important public service facilities because they safeguard peoples' health and lives.…”
Section: Introductionmentioning
confidence: 99%